Phenology of Migration and Decline in Colony Numbers and Crop Hosts of Giant Honeybee (Apis dorsata F.) in Semiarid Environment of Northwest India. (2nd December 2014) - Sihag, Ram Chander
Abstract : The colonies of the giant honeybee ( Apis dorsata ) immigrate in the semiarid environment of Northwest India in October-November with the onset of flowering on pigeon pea ( Cajanus cajan )/toria ( Brassica campestris var. toria), stay here during the rich pollen and nectar flow period from December to mid-May, and emigrate in late May/early June when floral dearth is witnessed. This honeybee was free from any conspicuous viral, bacterial, and fungal diseases and also did not have any serious predators and enemies. However, about 20 percent of the old colonies were infested with Tropilaelaps clareae and 100 percent of the old colonies with Galleria mellonella ; none of the swarm colonies had these pests. While the migration schedule of this honeybee remained similar year after year, the number of colonies immigrating in this region declined markedly over the years; the number in 2012 was even less than half of that recorded in 1984. During its stay in this region, this honeybee acted as an important pollinator of more than 30 crop plants of this region. The causes of seasonal migration and decline in the number of colonies of this honeybee and its importance in crop pollination have been discussed.